CORPORATE GOVERNANCE DETERMINANTS OF BANK FINANCIAL PERFORMANCE THROUGH GREEN BANKING IN INDONESIA - Dalimunthe, Ibram Pinondang; Gursida, Hari; Indrayono, Yohanes (jfpublisher, 2025)
The return on equity (ROE) is used as an indicator of profitability that is of concern to the bank’s internal and external parties; the pressure on the increasingly difficult environmental situation urges banks to be involved in their role in reducing the impact of damage without setting aside profitability. This research analyzes the effect of institutional ownership, managerial ownership, audit committee, independent commissioner, and ASEAN corporate governance scorecard on return on equity through disclosure of green banking practices in Indonesia. This research method uses a quantitative approach with secondary data. The sample of this study was 13 banks that were members of the Indonesian Sustainable Finance Initiative (IKBI) in 2018-2023, and they were analyzed by path analysis using SmartPLS version 4. The results indicate that institutional ownership negatively affects the green banking disclosure index, while managerial ownership, the audit committee, and independent commissioners show no effect. The ASEAN Corporate Governance Scorecard positively affects the index. In turn, the index positively influences return on equity (ROE). Institutional ownership does not affect ROE directly, but its negative impact is fully mediated by the disclosure index. Managerial ownership has a negative effect on ROE, while independent commissioners have a positive one; the audit committee and the governance scorecard show no direct effect on ROE. The disclosure index does not mediate the effects of managerial ownership, the audit committee, or independent commissioners on ROE, yet it fully mediates the positive effect of the governance scorecard.